(untitled) (Revista Internacional de Folkcomunicação, 2019)
This article intends to analyse how the folklore teaching is developed in Child Education and its contributions as didactic resourse in classroom. The carried out research is of qualitative and descriptive nature. We’ve chosen the survey as data collection instrument, which sought to gather information with teachers, research subjects and a Center for Early Childhood Education, in order to understand the local folklore teching practices. According to the teachers, folklore is present in the school environment as an interdisciplinary didactic resourse, facilitating pedagogic action and children’s learning about different aspects of folk cultural identity. Folklore; Childhood Education; Education.